1999
DOI: 10.1002/(sici)1096-9071(199911)59:3<318::aid-jmv10>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific prevalence and transmission of TT virus

Abstract: TT virus (TTV) is an unenveloped, single-stranded DNA virus that was discovered recently in the sera of Japanese patients with posttransfusion hepatitis of unknown etiology. A high prevalence of TTV infection in blood donors of several countries, including Brazil, has been demonstrated. To study the variation in TTV prevalence between different age groups, sera from 223 individuals without liver disease, aged 0-80 years, were tested by the polymerase chain reaction for the presence of TTV DNA. All subjects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
45
3

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 17 publications
9
45
3
Order By: Relevance
“…This group was quite representative of the population of the south of Brazil. Taken together with previous studies showing high prevalences (24-65%) of TTV infection in blood donors , parturient women (Saback et al 1999), and health care workers (Niel et al 2000) from Rio de Janeiro, as well as hepatitis patients from São Paulo and Pará states (Pinho et al 1998), the results presented here constitute additional evidence that a large part of the Brazilian population is chronically infected with TTV.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This group was quite representative of the population of the south of Brazil. Taken together with previous studies showing high prevalences (24-65%) of TTV infection in blood donors , parturient women (Saback et al 1999), and health care workers (Niel et al 2000) from Rio de Janeiro, as well as hepatitis patients from São Paulo and Pará states (Pinho et al 1998), the results presented here constitute additional evidence that a large part of the Brazilian population is chronically infected with TTV.…”
Section: Discussionsupporting
confidence: 85%
“…This corroborated observations made in Japan that showed a high prevalence in a preschool group, followed by a decline during the adolescence and a new elevation among young adults (Yamada-Osaki et al 1998). However, a similar curve of age-specific TTV seroprevalence was not observed among healthy individuals living in the city of Rio de Janeiro, where the prevalence, measured using the Tanaka´s PCR detection system, increased continuously with age (Saback et al 1999). The reasons which could explain this discrepancy are still not clear.…”
Section: Discussionmentioning
confidence: 88%
“…Transplacental or perinatal infection results in virus persistence, as observed in previous studies for established TT virus genotypes. [58][59][60] The expansion of susceptible cells in the course of a newborn child's development, as well as acquisition of new infections with additional TTV types during the first year of life, 49 should result in an increasing number of persistently infected cells and correspondingly to a steadily increasing viral load. It has recently been reported that TT virus concentrations increase with age.…”
Section: Target Cell Conditioning Modelmentioning
confidence: 99%
“…It has recently been reported that TT virus concentrations increase with age. 58 Partial homology of this viral DNA with host cell genes frequently engaged in translocations of leukemic or lymphoma cells should increase the risk for specific translocations in the course of viral and cellular DNA replication proportional to the number of viral DNA-positive cells. Occasionally, such translocations are also found in healthy individuals, as for example described for the lymphoma-associated translocation t(14;18).…”
Section: Target Cell Conditioning Modelmentioning
confidence: 99%
“…Viral particles have been purified from feces (17, 34) and, in addition, are excreted in saliva, breast milk, and bile juice (9,38,47,49). Transplacental transmission from mother to child has been controversial, but postnatal transmission has been confirmed repeatedly (15,20,24,30,33,37,48,51,52,57 (39,44). Peripheral blood mononuclear cells act as a reservoir for TTV (41), but the highest viral load is found in the granulocytes (54).…”
mentioning
confidence: 99%